Ответы и объяснения

2013-03-11T21:12:51+04:00

1)x^2 - 11x - 42 = 0

х=14  х=-3

 

2)-2x^2 - 5x - 2 = 0

D= 25-16=9

x= -0.5  x= -2

 

3)x^4-13x^2 + 36 = 0

x^2=9    x^2=4

x= -3  x= 3  x=-2  x=2

  • Участник Знаний
2013-03-11T21:44:53+04:00

1) x^2 - 11x - 42 = 0

  По теореме Виета :

   x1+x2= 11             x1= -3

   x1*x2= -42            x2=  14

Ответ: 14, -3 

2)-2x^2 - 5x - 2 = 0 |*-1

    2x^2+5x+2= 0

       -5+-√25-16

   x=---------------

              4

          -5+-3

    x= -----------

               4

   x= -2

   x= -1/2

Ответ: -2, -1/2

3)x^4-13x^2 + 36 = 0 

   Пусть x^2= t, тогда

  t^2-13t+ 36= 0

        13+-√169-144

   t=-----------------------

                   2

           13+-5

   t= ----------------

               2

  t= 9

  t= 4

Решим квадратное уравнение, где  x^2= t. получим:

 x^2= 9   и  x^2=  4

 х= 3           х= 2

 х=-3          х= -2

Ответ: 3, -3, 2, -2